Porous phosphate-based bioactive glass /β-TCP scaffold for tooth remineralization. - Criseida Ruiz-Aguilar (PLoS ONE, 2023)
The total or partial loss of teeth in the Mexican population due to periodontal diseases and trauma causes the development of other conditions, such as limitations in chewing and grinding food, pronunciation difficulties, and oral aesthetic alterations. In Mexico, oral diseases have been described to affect 87% of the population, according to reports by the health services, emphasizing that pregnant women and patients with diabetes mellitus have the highest risk of presenting with severe periodontal diseases or tooth loss, according to findings by the Mexican Health Department's Specific Action Program for the prevention, detection, and control of oral health problems (2013-2018). There was a 92.6% prevalence of dental caries in the population examined, and the prevalence of periodontal problems, mainly in 40-year-olds, was above 95%. The objective of this investigation was to manufacture and characterize porous 3D scaffolds with innovative chemical compositions, using phosphate-based bioactive glass, beta-phase tricalcium phosphate, and zirconium oxide, in variable quantities. The scaffold manufacturing method combined two techniques: powder metallurgy and polymer foaming. The results obtained in this research were promising since the mechanically tested scaffolds showed values of compressive strength and modulus of elasticity in the range of human trabecular bone. On the other hand, the in vitro evaluation of the samples immersed in artificial saliva at days 7 and 14 presented the calcium/phosphorus ratio = 1.6; this value is identical to the reported state-of-the-art figure, corresponding to the mineral phase of the bones and teeth. Likewise, the precipitation of the flower-like morphology was observed on the entire surface of the scaffold without zirconia; this morphology is characteristic of hydroxyapatite. On the other hand, the samples with 0.5 and 1.0 mol% zirconia showed less hydroxyapatite formation, with a direct correlation between scaffold dissolution and the amount of zirconia added.